Phylogenomic Study of Burkholderia glathei-like Organisms, Proposal of 13 Novel Burkholderia Species and Emended Descriptions of Burkholderia sordidicola, Burkholderia zhejiangensis, and Burkholderia grimmiae - Peeters, Charlotte; Meier-Kolthoff, Jan P.; Verheyde, Bart; De Brandt, Evie; Cooper, Vaughn S.; Vandamme, Peter (Frontiers in Microbiology, 2016)
Partial gyrB gene sequence analysis of 17 isolates from human and environmental sources revealed 13 clusters of strains and identified them as Burkholderia glathei clade (BGC) bacteria. The taxonomic status of these clusters was examined by whole-genome sequence analysis, determination of the G+C content, whole-cell fatty acid analysis and biochemical characterization. The whole-genome sequence-based phylogeny was assessed using the Genome BLAST Distance Phylogeny (GBDP) method and an extended multilocus sequence analysis (MLSA) approach. The results demonstrated that these 17 BGC isolates represented 13 novel Burkholderia species that could be distinguished by both genotypic and phenotypic characteristics. BGC strains exhibited a broad metabolic versatility and developed beneficial, symbiotic and pathogenic interactions with different hosts. Our data also confirmed that there is no phylogenetic subdivision in the genus Burkholderia that distinguishes beneficial from pathogenic strains. We therefore propose to formally classify the 13 novel BGC Burkholderia species as Burkholderia arvi sp. nov. (type strain LMG 29317T = CCUG 68412T), Burkholderia hypogeia sp. nov. (type strain LMG 29322T = CCUG 68407T), Burkholderia ptereochthonis sp. nov. (type strain LMG 29326T = CCUG 68403T), Burkholderia glebae sp. nov. (type strain LMG 29325T = CCUG 68404T), Burkholderia pedi sp. nov. (type strain LMG 29323T = CCUG 68406T), Burkholderia arationis sp. nov. (type strain LMG 29324T = CCUG 68405T), Burkholderia fortuita sp. nov. (type strain LMG 29320T = CCUG 68409T), Burkholderia temeraria sp. nov. (type strain LMG 29319T = CCUG 68410T), Burkholderia calidae sp. nov. (type strain LMG 29321T = CCUG 68408T), Burkholderia concitans sp. nov. (type strain LMG 29315T = CCUG 68414T), Burkholderia turbans sp. nov. (type strain LMG 29316T = CCUG 68413T), Burkholderia catudaia sp. nov. (type strain LMG 29318T = CCUG 68411T) and Burkholderia peredens sp. nov. (type strain LMG 29314T = CCUG 68415T). Furthermore, we present emended descriptions of the species Burkholderia sordidicola, Burkholderia zhejiangensis and Burkholderia grimmiae. The GenBank/EMBL/DDBJ accession numbers for the 16S rRNA and gyrB gene sequences determined in this study are LT158612-LT158624 and LT158625-LT158641, respectively.